Los Estudios Irlandeses en España 2021 - Teresa Caneda-Cabrera (Estudios Irlandeses, 2022)
If 2020 will always be remembered as the year when Covid 19 turned our world upside down, 2021 was the year we were all looking forward to as we hoped for a new time of healing and recovery. Still overwhelmed by the grief and loss we had experienced in the previous months, forced to live in the middle of unprecedented uncertainty on a global scale, one of the major challenges of 2021 has been (and continues to be as I write these lines in 2022) our having to cope with constant insecurity on many levels and in many different ways. In my role as the new chronicler for the section “Irish Studies in Spain”, I wish, first of all, to recognize and celebrate the fact that we have managed to develop extraordinary capacities to resist, to be resilient and to produce resources that have enabled us to connect, to communicate and to collaborate productively despite an ever-changing scenario of unpredictable and often adverse circumstances.